Maharashtra State BoardHSC Commerce 12th Board Exam
Advertisement Remove all ads

Solve the following equations by method of reduction : x + 2y – z = 3 , 3x – y + 2z = 1 and 2x – 3y + 3z = 2 - Mathematics and Statistics

Advertisement Remove all ads
Advertisement Remove all ads
Sum

Solve the following equations by method of reduction :

x + 2y – z = 3 , 3x – y + 2z = 1 and 2x – 3y + 3z = 2

Advertisement Remove all ads

Solution

Matrix form of the given system of equations is

`[(1, 2, 1),(3, -1, 2),(2, -3, 3)] [(x),(y),(z)] = [(3),(1),(2)]`

This is of the form AX = B, where

A = `[(1, 2, 1),(3, -1, 2),(2, -3, 3)], "X" =  [(x),(y),(z)] "and B"= [(3),(1),(2)]`

Applying R2 → R2 – 3R1 and R3 → R3 – 2R1, we get

`[(1, 2, 1),(0, -7, -1),(0, -7, 1)] [(x),(y),(z)] = [(3),(-8),(-4)]`

Applying R3 → R3 – R2, we get

`[(1, 2, 1),(0, -7, -1),(0, 0, 2)] [(x),(y),(z)] = [(3),(-8),(4)]`

Hence, the original matrix A is reduced to an upper triangular matrix.

∴ `[(x + 2y + z),(0 - 7y - zx),(0 + 0 + 2z)] = [(3),(-8),(4)]`

By equality of martices, we get
x + 2y + z = 3         ...(i)
– 7y –z = – 8
i.e., 7y + z = 8        ...(ii)
2z = 4
∴ z = 2
Substituting z = 2 in equation (ii), we get
7y + 2 = 8
∴ 7y = 6
∴ y = `(6)/(7)`
Substituting y = `6)/(7)` and z = 2 in equation (i), we get

`x + 2(6/7) + 2` = 3

∴ `x + 12/7 + 2` = 3

∴ x = `3 - 2 - 12/7 = (-5)/(7)`

∴ x = `(-5)/(7), y = (6)/(7)` and z = 2 is the required solution.

Concept: Application of Matrices
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×